Sensitivity of high‐resolution idealized simulations of thunderstorms to horizontal resolution and turbulence parametrization. (23rd May 2014) - Verrelle, A.; Ricard, D.; Lac, C.
<x xml:space="preserve">Abstract</x> Idealized simulations of deep moist convection are performed with the Meso‐NH model at kilometric scales to assess the impact of the horizontal grid spacing (4 km, 2 km, 1 km and 500 m) and turbulence scheme (one‐dimensional (T1D) versus three‐dimensional (T3D) turbulence). The simulations generate one cell which splits into two convective systems: a leftward‐moving multicellular system and a rightward‐moving supercell. Objective criteria based on statistical properties and bulk quantities are examined for both systems to characterize the convection. They show that the accumulated rainfall and corresponding surface area increase with increasing resolution, as does the area covered by the updraughts, while the 90th quantile of the intensity of updraught cores decreases. The 4 km horizontal grid spacing is set apart, as it clearly under‐resolves the convective motions, but the difference between 2 and 1 km horizontal resolutions is larger than between 1 km and 500 m, suggesting the beginning of convergence at 500 m. Also, 1 km appears to represent the deep convective structures more correctly than 2 km for a practical weather forecast of organized convective systems. T3D induces more mixing and enhances the microphysical processes compared with T1D, producing larger amounts of cloud cover and precipitation. Also, the magnitude of the pressure anomaly on the southeastern flank of the supercell is stronger, accentuating the path curvature. The difference between T1D and T3D becomes perceptible at 2 km, pointing out the necessity to deal with horizontal turbulent fluxes at kilometric resolutions. Although a stronger numerical diffusion added to T1D allows the necessary damping to be introduced at the spectral energy tail, it removes a part of the physical mixing and still misses some variance at larger scales. The ratio between resolved and total turbulent kinetic energy (TKE) decreases with increasing resolution for both T1D and T3D, which is unexpected. The main explanation is insufficient turbulent mixing inside convective clouds, more pronounced at coarser resolution, which is also confirmed by the vertical velocity spectra. At 500 m horizontal resolution, the subgrid TKE is mainly due to dynamical processes, with maxima located at the upper level of the convective systems in areas of stronger potential temperatures associated with downdraughts. However, thermal production is mostly negative, underlying the lack of entrainment at the cloud edges.